Resultados de los instrumentos evaluativos aplicados en la asignatura de historia para bachillerato. - Revelo, Marieta I. (2022)
The evaluation instruments of the educational process have been diversifying over time. In Baccalaureate, these instruments try to capture the attention of the students, combining academic fundamentals with innovative criteria. The objective of this research work is to present the results of the evaluation instruments that have been used for the learning of the subject of History in the students of the Unified General Baccalaureate. For this, it is proposed to address this problem from the question: how do the evaluation techniques and instruments affect the students in the learning of the subject of History in the Unified General Baccalaureate, of the Educational Unit "Carlos Martínez Acosta" of the City of Mira, during the 2021-2022 school period? The methodology used is based on a qualitative and descriptive approach, while as techniques, the interview with open questions was applied to five (5) Teachers of the Social Sciences Area of the institution, and the survey to fifty (50) students. The results of this work yielded relevant data such as the fact that the majority of students consider that teachers never apply assessment instruments during class hours, while teachers refuted this criterion stating the opposite. In addition, teachers and students agree that new assessment instruments should be used, such as the rubric, the portfolio and the PBL, among others. It is concluded that innovation in evaluation instruments motivates students and improves the educational process.